Community Satisfaction Analysis of Organic Waste Management: A Case Study of Compost Houses and 3R Waste Collection Sites in Barru Regency - Asriani; Syamsiah (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal